POTENSI ANTIOKSIDAN DAN SKRINING FITOKIMIA EKSTRAK DAUN MANGROVE Rhizophora mucronata, PILANG PROBOLINGGO - Kasitowati, Rarasrum Dyah; Yamindago, Ade; Safitri, Mila (Faculty of Fisheries and Marine Science, Brawijaya University, Malang, Indonesia, 2017)
The objective of this study was to find out the antioxidant activities along with phytochemical screening of R. mucronata leaf extracts. R. mucronata leaves were collected from Pilang, Probolinggo. The extraction use three different solvents with different polarity (Methanol, Ethyl acetate, and Hexane). The antioxidant activities were determinted by the Diphenyl picryhydrazil (DPPH) metode used four different concentrations (31,25; 62,25; 125; and 250 ppm). The antioxidant analysis of mangrove R. mucronata showed that the ethyl acetate extract has the highest antioxidant activity (160,417 µg/ml) than the methanol (-117,498 µg/ml) and the hexane (327,611 µg/ml) extracts. The phytochemical screening results that the methanol extract contains 1195 µg/ml flavonoid compounds, 124,44 µg/ml alkaloid compounds and 576,64 µg/ml of tannin compounds. Meanwhile the ethyl and the hexane extract contains alkaloid compounds (44,91 µg/ml and 41,49 µg/ml ) and tannin compounds (84,84 µg/ml and 67,30 µg/ml).